2015
DOI: 10.1016/j.envpol.2015.08.008
|View full text |Cite
|
Sign up to set email alerts
|

Differential embryotoxicity of the organic pollutants in rural and urban air particles

Abstract: Airborne particulate matter (PM) is a recognized risk factor for human populations. Here we assessed the toxic potential of the organic constituents from PM collected in urban and rural sites during warm and cold periods of 2012/2013, and fractionated into 6 size fractions. The finest PM fraction (<0.5 μm) showed the highest biological activity (dioxin-like activity and fish embryotoxicity) in all samples, and the maximal activity was observed in rural samples from the cold period. Zebrafish embryo transcripto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
19
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 54 publications
1
19
0
Order By: Relevance
“…Epidemiologic studies have suggested an increased risk of congenital heart defects (CHD) in the offspring of mothers exposed to ambient air pollution and PM2.5 . Zebrafish is an ideal vertebrate animal model for investigating cardiac development, and we and others have shown that extractable organic matter (EOM) from PM2.5 has adverse effects on heart development in zebrafish embryos …”
Section: Introductionmentioning
confidence: 99%
“…Epidemiologic studies have suggested an increased risk of congenital heart defects (CHD) in the offspring of mothers exposed to ambient air pollution and PM2.5 . Zebrafish is an ideal vertebrate animal model for investigating cardiac development, and we and others have shown that extractable organic matter (EOM) from PM2.5 has adverse effects on heart development in zebrafish embryos …”
Section: Introductionmentioning
confidence: 99%
“… 3 The carcinogenic potential of PAH has been known since 1776, 22 but their effects on the nervous system, particularly the developing nervous system, have come to light only in the recent past. 23 It has been postulated that PAH may damage the developing fetal brain by increasing oxidative stress 24 , 25 and causing vascular injury. 26 Several epidemiological studies have found an association between in utero exposure to PAH and neurodevelopment and behavior.…”
Section: Introductionmentioning
confidence: 99%
“…This is a transcription factor activated by a large number of ligands, including PAHs [82,83,85,86] and involved in many cell processes. For example, extractable organic matter (EOM) from PM2.5 may cause heart malformations and decreased heart rates in zebrafish embryos through the AhR, and these heart defects appear to be counteracted in embryos co-exposed to EOM and an AhR antagonist [87,88]. Concerning the male reproductive system, Izawa et al have reported a decrease in the daily production of spermatozoa, an increase in morphological abnormalities in spermatozoa as well as a significant increase in blood testosterone levels in the group exposed to diesel exhaust combined with a significant increase in the AhR activity index [89].…”
Section: Action As Endocrine Disruptorsmentioning
confidence: 99%